Unlocking Opportunities: Building Skills And Mindset In The Digital Age - Frischa Faradilla Arwinda Mongan; Nuraisyiah Nuraisyiah; Muchriana Muchran; Saida Said; Sitti Zulaeha (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This community service program, entitled Unlocking Opportunities: Building Skills and Mindset in the Digital Age, was carried out at Sangkhom Islam Wittaya School, Hat Yai, Thailand. The program aimed to strengthen students’ digital literacy, entrepreneurial awareness, cross-cultural communication, and growth mindset as essential 21st-century skills. The activities were designed in the form of interactive workshops, cross-cultural group discussions, hands-on practices, and reflective sessions. Seventy students aged 13 to 16 actively participated in the program. The implementation demonstrated that the integration of experiential learning and international collaboration significantly improved students’ knowledge, skills, and attitudes. Structured presentations effectively enhanced competence, while simulation activities and group discussions built confidence and character. Moreover, the cross-cultural exchange fostered stronger connections and caring attitudes among participants. The final outcomes showed that students developed greater adaptability, creativity, and awareness of global citizenship. In conclusion, the program successfully contributed to empowering youth in Hat Yai through an interdisciplinary and holistic approach to education. The results confirmed the importance of combining digital literacy, leadership training, and cultural collaboration to prepare young learners for global challenges in the digital age. This initiative also opened opportunities for sustainable international partnerships in community service and youth empowerment.